2019
DOI: 10.1111/mve.12405
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory responses of Amblyomma maculatum to rumen fluid and other odourants that attract blood‐seeking arthropods

Abstract: Amblyomma maculatum Koch (Ixodida: Ixodidae) has emerged as a significant vector of human and companion animal diseases in the U.S.A. When expanding in range, A. maculatum can be difficult to collect in the field and control on livestock. A novel method is needed to improve the field collection of A. maculatum, as well as to control their effects as ectoparasites of livestock and companion animals. The present study aimed to test the effects of known volatiles on the activation and selection choices of A. macu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The lack of antennae, the presence of very few olfactory sensilla, the development of a distinctive organ (Haller’s) used for volatile detection, and the multimodal role of sensilla located on mouthparts make ticks a fascinating system for understanding how chelicerates (and particularly Ixodidae) detect chemicals [ 4 , 5 , 6 ]. Previous studies have focused on investigating tick responses to attractant stimuli, such as chemicals emitted by suitable hosts (CO 2 , typical human odors, or compounds produced by vertebrates) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Moreover, there are several examples of behavioural bioassays used to validate the repellent activity of compounds from synthetic and natural origin, allowing isolation of potential new active ingredients for the development of more effective tick repellent products [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of antennae, the presence of very few olfactory sensilla, the development of a distinctive organ (Haller’s) used for volatile detection, and the multimodal role of sensilla located on mouthparts make ticks a fascinating system for understanding how chelicerates (and particularly Ixodidae) detect chemicals [ 4 , 5 , 6 ]. Previous studies have focused on investigating tick responses to attractant stimuli, such as chemicals emitted by suitable hosts (CO 2 , typical human odors, or compounds produced by vertebrates) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Moreover, there are several examples of behavioural bioassays used to validate the repellent activity of compounds from synthetic and natural origin, allowing isolation of potential new active ingredients for the development of more effective tick repellent products [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Each tick was marked with one of five colors of fluorescent powder (Day-glo ECO pigments™, Day-glo Color Corp., Cleveland, OH) and returned to their respective plastic containers to rest. The markers were previously evaluated in the laboratory with no significant effect on activity (Garner et al 2020). After 24 hours, one tick of each sex of each color was put into each of six mesh cages.…”
mentioning
confidence: 99%
“…The latest studies indicated the importance of A. maculatum as a vector of tick-borne pathogens affecting humans and animals that might be increasing in the region (Paddock et al 2015, Noden et al 2020). While the off-host activity period for A. maculatum might be long within a 24-hour period, there is need to continue evaluating ways to improve collection of this important tick species even if it includes use of rumen volatiles that seem to attract ticks short distances (Garner et al 2020).…”
mentioning
confidence: 99%